769 Analysing the Change – Outcomes and Benefits of Clinic-Based Removal of Renal Transplant Stents Using A Disposable Cystoscope. (4th May 2021) - Chowdary, P; Shetty, S; Whittaker, C; Prasad, M; Mohamed, I; Khurram, M
Abstract: Introduction: Literature is chock-full of data regarding the "when" of ureteric stent removal after renal transplantation. We have attempted to address the "who", "where" and "how" components. Method: The Isiris disposable scope was used to remove renal allograft stents from 383 patients in the Transplant Clinic from June 2018 to April 2020. An advanced nurse practitioner was trained in the procedure. The learning curve, incidence of complications, benefits and cost implications were studied, and compared with the cohort having stent removal with a traditional flexible cystoscope in theatres. Results: There were 14 failures necessitating theatre removal. The transplant-to-stent-removal interval was significantly lower in the clinic cohort with a mean of 38.80 days (95%CI 37.26–40.34) to 46.55 days in theatres (95%CI 43.47–49.62). 11 patients had urgent bedside stent removal. The service was delivered independently by the nurse for 5.3% of the patients in June 2018 and progressed to over 80% by April 2019. Estimated net gain was £919/patient. Conclusions: Moving transplant ureteric stent removals from a resource intensive all-day process in theatres to a one-stop event in the clinic is a safe and economical model that can streamline flow in patient pathway and inculcate new skills in other members of the multidisciplinary team.